Physical purity of cowpea seeds from trained community based and licensed seed producers in three states of Nigeria - Iyorkaa, N.; Omoigui, L.; Odo, P.E.; Kamara, A.; Ugbaa, M.S.; Ekeuro, G.C. (2021)
The study was conducted to compare two main sources of cowpea seed, Community Based Seed Producers (CBSP) and Licensed Seed Producers (LSP) for physical purity indices. From each seed source in every state, 15 seed samples of between 2 to 3 kg were collected for seed quality analysis. The collected seed samples were bulked according to variety, state, and seed source and then reduced to a working sample of four (4kg) using a modified halving method. The 4 kg was then divided into four equal parts as replicates. Seed purity was measured by sorting 1 kg of each working sample. The treatments were laid out in a completely Randomized Design (CRD) with four replications in the Molecular Biology Laboratory, Federal University of Agriculture, Makurdi. The experiment was set up as a factorial combination on pure seeds, using 2 (seed source) × 3 (States) × 3 (varieties). Data were collected on the following parameters; Percentage Pure Seed, Percentage Inert Matter, Percentage Offtypes seeds, Percentage Field Insect Damaged Seeds, Percentage Rain Damaged Seed, Percentage Weevil Damaged Seeds and Percentage Seeds Moisture Content and was analyzed was carried out using Minitab, version 2017. Seeds from the different states were statistically comparable. However, for varieties, cowpea seeds were not comparable except for rain damage and inert matter. On seed source, community-based seed producers performed below the licensed seed producers with respect to seeds damaged by rain, field insect damage, inert matter, weevil damage, pure seeds and moisture content. They were however, comparable in terms of off-types and mater. The two seed sources however, met the minimum standard required for cowpea seed certification by the National Agricultural Seed Council (NASC) with respect to off types and inert matter and hence could be used as an alternative seed source without any serious disadvantage of seeds purity. Therefore, we concluded that farmers can obtain seed from community-based seed producers without any serious disadvantage in terms of purity of seed lot.